Garap Gerak Tari Ronggeng Paser di Kabupaten Paser Kalimantan Timur - Wulandari, Andrea; MD, Slamet; Maharani Lutvinda Dewi (Universitas Negeri Medan, 2025)
The research aims to analyze and describe the form and movement of the Ronggeng Paser dance. Answering the problem of dance forms using the concept of Slamet MD that choreography is known as a dance form that cannot be separated from elements. To answer the problem of motion work using Slamet MD work theory, the concept of solah-ebrah, solah is movement and ebrah is form. The method used is a qualitative research type. Data collection techniques include observation, interviews, and literature studies. The results of the study show that the form concists of elements that are arranged in the Ronggeng Paser dance, including movement, dancers, make-up, costume, floor patterns, dance music and performance venue. And work on the movement by looking at the trajectory, dynamics, volume, tempo that forms the main movement pattern, alternating movements, and variation movements so that a variety of movements are created that have character as an element in the formation of dance that is placed according to the character called estra.